(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1995)
Shell-beds rich in shell fragments are very common in the Lombardia basinal facies in the Late Triassic. Biofragmentation by durophagous fishes, which were very common, must be regarded as the main taphonomic process on the basis of the shape of fragments and the presence of predatory traces, such as semicircular notches on the fragment edges or punctures on whole valves. Scattered patches of shell-fragments are also common and are considered as ejecta and/or coprolites from durophagous fishes. Funhermore, shell material fragmented by living fish (Pogonias cromis and Diplodus sargus among others) is comparable in shape with the Triassic material presented here. The shell-beds here described were deposited in a low energy environment, which precludes waves or currents mechanical damages. Paralepidotus ornatus, the most common Triassic duropagous fish, pycnodonts, other semionotids and the placodont reptile Psephoderrna alpinum, are the most important shell-predators in the Late Triassic. Modiolus, Laternula and Protocardia were the more commonly preyed molluscs.